2017
DOI: 10.1007/s10517-017-3784-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of Proliferative Activity of Vaginal Epithelium in Women with Stress Urinary Incontinence Treated by Er:YAG Laser

Abstract: The expression of Ki-67 proliferation marker was studied in vaginal biopsy specimens from women with stress urinary incontinence treated using a Fotona nonablative erbium laser. Cells expressing Ki-67 were located in all cases in the parabasal and basal levels of stratified squamous epithelium, the index of labeled nuclei before Er:YAG laser exposure was 19.05±2.86%. After 1-2 months of laser therapy, the index of labeled nuclei in the epithelium increased significantly and reached 31.79±2.25%. These changes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…Seventeen studies counting more than 892 female patients with UI were included in the review. 4,8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The search of MEDLINE and SCOPUS provided a total of 878 records. After removing duplicates, 526 studies were excluded because they did not meet the criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies counting more than 892 female patients with UI were included in the review. 4,8,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] The search of MEDLINE and SCOPUS provided a total of 878 records. After removing duplicates, 526 studies were excluded because they did not meet the criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, studies comprising histopathological investigation found increased proliferative activity, remodelling of the stromal components of vaginal mucosa, higher synthesis of collagen and neoangiogenesis. 25,26 The majority of the patients tolerated treatments well; few of them reported minor symptoms during laser sessions, which ranged from mild discomfort to warmth sensation. Only one patient quitted treatment due to intolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human soft tissue, the 2940 nm erbium yttrium‐aluminum‐garnet medium (Er:YAG) laser in the non‐ablative thermal mode has been shown to stimulate deep collagen remodeling and improve tightness and elasticity of the treated area . This non‐ablative treatment modality has been evaluated in several studies . A study evaluating Er:YAG laser treatment compared with topical estrogen therapy for GSM‐related symptoms demonstrated greater improvement in symptoms (irritation, dyspareunia, dryness, chronic leukorrhea) of the laser‐treated group up to 18 months of follow‐up after treatment.…”
Section: Discussionmentioning
confidence: 99%